Gender Disparities and Board Representation in Zimbabwe - Magomana, Nzwirashe R.; Mkhize, Msizi; Abel, Sanderson; Aliamutu, Kansilembo (International Journal of Economics and Financial Issues, 2024)
Approximately one-third of the world’s GDP is held by the 500 biggest firms worldwide. Nonetheless, barely 25% of Fortune 500 board members and <6.7% of board chairs worldwide were female in 2021. The aim of this paper is to understand and address gender disparities in the private sector. The study investigated thirty-six companies with the aid of a structured questionnaire. The study used a mixed research design. It explored the qualitative aspects of the board gender gap through interviews, followed by a quantitative phase to validate and enrich the findings. The findings demonstrated that women were noticeably underrepresented on corporate boards. The gender disparity that exists in Zimbabwe is evidently shown in the results. The findings also highlight subtle differences in the power and decision-making procedures on boards. The implication of the results is that there is need for deliberate efforts to enhance gender diversity at the leadership level to ensure inclusivity and effective governance. Strategies that promote equal opportunities and mitigate gender-based biases are essential for fostering a more inclusive and equitable corporate environment.